A moment's monument Medardo Rosso and the international origins of modern sculpture - Hecker, Sharon (University of California Press, 2017)
"Medardo Rosso (1858-1928) is one of the most original and influential figures in the history of modern art, and this book is the first historically substantiated critical account of his life and work. An innovative sculptor, photographer, and draughtsman, Rosso was a key figure in the transition from the traditional forms of sculpture that persisted through the nineteenth century to the experimental forms that developed in the twentieth. His antimonumental, antiheroic work reflected alienation in the modern experience yet also showed deep feeling for interactions between self and other. Rosso's art was also transnational: he refused allegiance to a single culture or artistic heritage and declared himself both a citizen of the world and a maker of art without national limits. In this book, Sharon Hecker develops a narrative that is an alternative to the dominant Franco-centered perspective on the origin of modern sculpture in which Rodin plays the role of lone heroic innovator. Offering an original way to comprehend Rosso, A Moment's Monument negotiates the competing cultural imperatives of nationalism and internationalism that shaped the European art world at the fin de siècle"...Provided by publisher
Includes bibliographical references and index
Keywords: Rosso, Medardo -- 1858-1928 -- Criticism and interpretation; Rosso, Medardo -- 1858-1928; Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1880-1910; Sculpture, Italian -- 19th century; Sculpture, Italian -- 20th century; Plastik